Mangrove blue carbon strategies for climate change mitigation are most effective at the national scale. (24th October 2018) - Taillardat, Pierre; Friess, Daniel A.; Lupascu, Massimo
Abstract : Carbon fixed by vegetated coastal ecosystems (blue carbon) can mitigate anthropogenic CO2 emissions, though its effectiveness differs with the spatial scale of interest. A literature review compiling carbon sequestration rates within key ecosystems confirms that blue carbon ecosystems are the most efficient natural carbon sinks at the plot scale, though some overlooked biogeochemical processes may lead to overestimation. Moreover, the limited spatial extent of coastal habitats minimizes their potential at the global scale, only buffering 0.42% of the global fossil fuel carbon emissions in 2014. Still, blue carbon plays a role for countries with moderate fossil fuel emissions and extensive coastlines. In 2014, mangroves mitigated greater than 1% of national fossil fuel emissions for countries such as Bangladesh, Colombia and Nigeria. Considering that the Paris Agreement is based on nationally determined contributions, we propose that mangrove blue carbon may contribute to climate change mitigation at this scale in some instances alongside other blue carbon ecosystems.